UPAYA MENINGKATKAN KINERJA TENAGA PENDIDIK DI UNIVERSITAS ANDALAS: EVALUASI PADA REMUNERASI DAN STRES KERJA - Wahyu Adhi Pratama; Hendra Lukito (Journal Publicuho, 2025)
This study aims to test and assess the effect of remuneration on staff performance through work stress at Andalas University. A total, eighty staff participated and gave their true responses to the online questionnaires proposed. Then, it was analysed with the structural equation model technique by the assistance of SmartPLS software version 3 (SEM-PLS). The result shows that the mediating contribution of work stress did not significantly contribute to the relationship between remuneration and staff performance, but the direct effect of remuneration on staff performance was significant. These results also indicate that the level of staff stress at the Andalas University sis till in control and has no significant effect on performance.